Existence results for the p-Laplacian with nonlinear boundary conditions - Bonder, J.F. (2001)
In this paper we study the existence of nontrivial solutions for the problem Δpu = up-2u in a bounded smooth domain Ω ⊂ ℝN, with a nonlinear boundary condition given by |∇u|p-2∂u/∂v = f(u) on the boundary of the domain. The proofs are based on variational and topological arguments. © 2001 Academic Press.